HAPPINESS VARIES AT DIFFERENT PERIODS OF DEVELOPMENT - Madhok, Sushma (Innovative Research Thoughts, 2017)
At different points in the development process, happiness is varied. The happiest time in a person's life is when they are a child, and the most miserable time is when they are a teen. The way a kid is raised has a significant impact on his or her patterns of happiness, which differ from child to child. Findings by psychologists in their hunt for happiness indicators have been startling. Despite popular belief, many of the things that spring to mind when thinking about what makes us happy don't seem to have much of an impact. Social connections have been shown to be the most closely associated with high levels of happiness. Study after study has found that those who have strong social ties tend to report higher levels of happiness and contentment. Relationship quality and relationship satisfaction seem to have the strongest relationships with subjective well-being, as they do in other areas.